Antiapoptotic activity of Coxiella burnetii effector protein AnkG is controlled by p32-dependent trafficking - Eckart, Rita; Bisle, Stephanie; Schulze-Luehrmann, Jan; Wittmann, Irene; Jantsch, Jonathan; Schmid, Benedikt; Berens, Christian; Lührmann, Anja (Infection and Immunity, 2014)
Intracellular bacterial pathogens frequently inhibit host cell apoptosis to ensure survival of their host, thereby allowing bacterial propagation. The obligate intracellular pathogen Coxiella burnetii displays antiapoptotic activity which depends on a functional type IV secretion system (T4SS). Accordingly, antiapoptotic T4SS effector proteins, like AnkG, have been identified. AnkG inhibits pathogen-induced apoptosis, possibly by binding to the host cell mitochondrial protein p32 (gC1qR). However, the molecular mechanism of AnkG activity remains unknown. Here, we demonstrate that ectopically expressed AnkG associates with mitochondria and traffics into the nucleus after apoptosis induction, although AnkG lacks a predicted nuclear localization signal. We identified the p32 interaction region in AnkG and constructed an AnkG mutant (AnkG) unable to bind to p32. By using this mutant, we found that intracellular localization and trafficking of AnkG into the nucleus are dependent on binding to p32. Furthermore, we demonstrated that nuclear localization of AnkG but not binding to p32 is required for apoptosis inhibition. Thus, the antiapoptotic activity of AnkG is controlled by p32-mediated intracellular trafficking, which, in turn, seems to be regulated by host cell processes that sense stress. © 2014, American Society for Microbiology.

Crystal Structure of the Extracellular Domain of the Human Dendritic Cell Surface Marker CD83 - Heilingloh, Christiane; Klingl, Stefan; Egerer-Sieber, Claudia; Schmid, Benedikt; Weiler, Sigrid; Mühl-Zürbes, Petra; Hofmann, Jörg; Stump, Joachim; Sticht, Heinrich; Kummer, Mirko; Steinkasserer, Alexander; Muller, Yves (Journal of Molecular Biology, 2017)
Keywords: homotypic interactions; immune co-stimulation and -suppression; structure–function relationships; V-set Ig-domain; X-ray crystallography

Development of a yeast-based screening system for the identification of allergenic determinants of profilins - Paulus, Kathrin; Schmid, Benedikt; Mahler, Vera; Sonnewald, Uwe (Allergy, 2013)

Helicobacter pylori CagL Y58/E59 mutation turns-off type IV secretion-dependent delivery of CagA into host cells - Tegtmeyer, Nicole; Lind, Judith; Schmid, Benedikt; Backert, Steffen (PLoS ONE, 2014)
The type IV secretion system (T4SS) is a major virulence determinant of the gastric pathogen Helicobacter pylori. The CagL protein is a specialized adhesin of the corresponding T4SS pilus, which establishes initial contact with the integrin β1 receptor on host target cells. Recent studies proposed that Y58 and E59 amino acid polymorphisms in CagL increase the virulence of H. pylori strains by enhanced translocation and phosphorylation of the CagA effector protein. These polymorphisms were therefore correlated with an increased risk of gastric cancer development. Here we show that the Y58/E59 motif, which is located in a loop connecting two α-helices, and corresponding polymorphisms could influence the function of CagL. However, expression of isogenic CagL Y58/E59 variants in H. pylori strain 26695 significantly blocked the translocation and phosphorylation of CagA as compared to complemented wild-type CagL. These results suggest that the function of the T4SS for delivery of CagA is turned-off by the Y58/E59 mutation in CagL. This activity appears to be similar to the one recently described for another T4SS pilus protein, CagY, which is also sufficient to cause gain or loss of T4SS function. These data support the hypothesis that certain mutations in CagL or recombination events in CagY may serve as a sort of molecular switch or perhaps rheostat in the T4SS, which could alter the function of the pilus and "tunes" injection of CagA and host pro-inflammatory responses, respectively. © 2014 Tegtmeyer et al.

Hypoallergenic profilin - A new way to identify allergenic determinants - Paulus, Kathrin; Schmid, Benedikt; Zajic, Doreen; Schaefer, Alice; Mahler, Vera; Sonnewald, Uwe (Febs Journal, 2012)
Plant profilins are important panallergens, contributing to numerous food and pollen allergies. They fulfil essential functions in all eukaryotic cells, including yeast and mammals, making breeding of profilin-deficient crop plants an impossible task. To obtain hypoallergenic profilin-variants, a novel yeast based screening system to select for fully active but hypoallergenic profilins was developed. Despite similar biological functions, plant profilins share only limited amino acid sequence identity to nonplant profilins. Thus, it should be possible to select for hypoallergenic profilin variants that have kept their biological function. These variants were subsequently tested for IgE-binding and their 3D folding was analyzed. As prerequisites, we developed a conditional profilin-deficient yeast mutant strain and made use of a newly-discovered profilin variant from tomato that enabled pre-selection for efficient mutagenesis. After random mutagenesis and transformation of tomato profilin (Lyc e 1) into the designed yeast strain, we were able to screen for functional tomato profilin variants. Testing these variants for IgE binding revealed that two variants showed a strong reduction in IgE binding of four Lyc e 1 sensitized patients and one birch pollen allergic patient. This result, for the first time, provides strong evidence that selection of hypoallergenic Lyc e 1 variants is possible. Furthermore, this knowledge provides the basis for the molecular breeding of hypoallergenic profilin alleles in tomato. Plant profilins are important panallergens. They fulfil essential functions in all eukaryotic cells, making breeding of profilin-deficient crop plants an impossible task. To obtain hypoallergenic profilin-variants, a novel yeast-based screening system was developed. Testing profilin-variants for IgE binding revealed two variants with reduced IgE binding to sera from four Lyc e 1 sensitized patients and one birch pollen allergic patient. © 2012 The Authors Journal compilation © 2012 FEBS.
Keywords: birch allergy; Lyc e 1; PFY1; profilin; tomato allergy

Manipulation of charge distribution in the arginine and glutamate clusters of the OmpG pore alters sugar specificity and ion selectivity - Schmitt, Christine; Bafna, Jayesh Arun; Schmid, Benedikt; Klingl, Stefan; Baier, Steffen; Hemmis, Birgit; Wagner, Richard; Winterhalter, Mathias; Voll, Lars (Biochimica Et Biophysica Acta-Biomembranes, 2019)
OmpG is a general diffusion pore in the E. coli outer membrane with a molecular architecture comprising a 14-stranded β-barrel scaffold and unique structural features. In contrast to other non-specific porins, OmpG lacks a central constriction zone and has an exceptionally wide pore diameter of about 13 Å. The equatorial plane of OmpG harbors an annulus of four alternating basic and acidic patches whose function is only poorly characterized. We have investigated the role of charge distribution for ion selectivity and sugar transport with the help of OmpG variants mutated in the annulus. Substituting the glutamate residues of the annulus for histidines or alanines led to a strong reduction in cation selectivity. Replacement of the glutamates in the annulus by histidine residues also disfavored the passage of pentoses and hexoses relative to disaccharides. Our results demonstrate that despite the wide pore diameter, an annulus only consisting of two opposing basic patches confers reduced cation and monosaccharide transport compared to OmpG wild type. Furthermore, randomization of charged residues in the annulus had the potential to abolish pH-dependency of sugar transport. Our results indicate that E15, E31, R92, R111 and R211 in the annulus form electrostatic interactions with R228, E229 and D232 in loop L6 that influence pH-dependency of sugar transport.
CRIS-Team Scopus Importer:2019-08-20
Keywords: E. coli; Ion selectivity; Liposome swelling assay; Porin engineering; Reversal potential; Sugar specificity

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-alpha 1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagkoeylue, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2017)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its antiapoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-a1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-a1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-a1 is crucial for nuclear localization of AnkG.
EVALuna2:7733

Nuclear trafficking of the anti-apoptotic Coxiella burnetii effector protein AnkG requires binding to p32 and Importin-α1 - Schäfer, Walter; Eckart, Rita; Schmid, Benedikt; Cagköylü, Hasret; Hof, Kerstin; Muller, Yves; Amin, Bushra; Lührmann, Anja (Cellular Microbiology, 2016)
The obligate intracellular bacterium Coxiella burnetii causes the zoonotic disease Q-fever. Coxiella pathogenesis depends on a functional type IV secretion system (T4SS). The T4SS effector AnkG inhibits pathogen-induced host cell apoptosis, which is believed to be important for the establishment of a persistent infection. However, the mode of action of AnkG is not fully understood. We have previously demonstrated that binding of AnkG to p32 is crucial for migration of AnkG into the nucleus and that nuclear localization of AnkG is essential for its anti-apoptotic activity. Here, we compared the activity of AnkG from the C. burnetii strains Nine Mile and Dugway. Although there is only a single amino acid exchange at residue 11, we observed a difference in anti-apoptotic activity and nuclear migration. Mutation of amino acid 11 to glutamic acid, threonine or valine results in AnkG mutants that had lost the anti-apoptotic activity and the ability to migrate into the nucleus. We identified Importin-α1 to bind to AnkG, but not to the mutants and concluded that binding of AnkG to p32 and Importin-α1 is essential for migration into the nucleus. Also during Coxiella infection binding of AnkG to p32 and Importin-α1 is crucial for nuclear localization of AnkG.
EVALuna2:7709

Recombinant protein production and purification of SiiD, SiiE and SiiF - Components of the SPI4-encoded type I secretion system from Salmonella Typhimurium - Klingl, Stefan; Kordes, Sina; Schmid, Benedikt; Gerlach, Roman; Hensel, Michael; Muller, Yves (Protein Expression and Purification, 2020)
In humans, Salmonella enterica infections are responsible for a plethora of medical conditions. These include intestinal inflammation and typhoid fever. The initial contact between Salmonella and polarized epithelial cells is established by the SPI4-encoded type I secretion system (T1SS), which secretes SiiE, a giant non-fimbrial adhesin. We have recombinantly produced various domains of this T1SS from Salmonella enterica serovar Typhimurium in Escherichia coli for further experimental characterization. We purified three variants of SiiD, the periplasmic adapter protein spanning the space between the inner and outer membrane, two variants of the SiiE N-terminal region and the N-terminal domain of the SiiF ATP-binding cassette (ABC) transporter. In all three proteins, at least one variant yielded high amounts of pure soluble protein. Secondary structure content and cooperative unfolding were investigated by circular dichroism (CD) spectroscopy. Secondary structure contents were in good agreement with estimates derived from SiiD and SiiF homology models or, in case of the SiiE N-terminal region, a secondary structure prediction. For one SiiD variant, protein crystals could be obtained that diffracted X-rays to approximately 4 Å resolution.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Protein expression; Purification; Salmonella; Type I secretion system (T1SS)

Structural insight into the giant Ca²?-binding adhesin SiiE: implications for the adhesion of Salmonella enterica to polarized epithelial cells - Grießl, Martin; Schmid, Benedikt; Kaßler, Kristin; Braunsmann, Christoph; Ritter, Regina; Barlag, Britta; Stierhof, York-Dieter; Sturm, Karina U.; Danzer, Claudia Agnes; Wagner, Carolin; Schaeffer, Tilman E.; Sticht, Heinrich; et al. (Structure, 2013)
SiiE from Salmonella enterica is a giant 5,559-residue-long nonfimbrial adhesin that is secreted by a type 1 secretion system (T1SS) and initiates bacterial adhesion to polarized host cells. Structural insight has been gained into the 53 bacterial Ig-like (BIg) domains of SiiE, which account for 94% of the entire SiiE sequence. The crystal structure of a fragment comprising BIg domains 50 to 52 of SiiE reveals the BIg domain architecture and highlights two types of SiiE-specific Ca²?-binding sites. Sequence homology considerations suggest that full-length SiiE interacts with more than 100 Ca²? ions. Molecular dynamics simulations and single-molecule imaging indicate that Ca²? binding confers SiiE with a rigid 200 nm rod-like habitus that is required to reach out beyond the Salmonella lipopolysaccharide layer and to promote adhesion to host cells. The crystal structure suggests plausible routes for the establishment of the initial contact between Salmonella and host cells.
EVALuna2:7643

The Coxiella burnetii T4SS effector protein AnkG hijacks the 7SK small nuclear ribonucleoprotein complex for reprogramming host cell transcription - Cordsmeier, Arne; Rinkel, Sven; Jeninga, Myriam; Schulze-Lührmann, Jan; Oelke, Martha; Schmid, Benedikt; Hasler, Daniele; Meister, Gunter; Haecker, Georg; Petter, Michaela; Beare, Paul A.; Lührmann, Anja (PLoS Pathogens, 2022)
Inhibition of host cell apoptosis is crucial for survival and replication of several intracellular bacterial pathogens. To interfere with apoptotic pathways, some pathogens use specialized secretion systems to inject bacterial effector proteins into the host cell cytosol. One of these pathogens is the obligate intracellular bacterium Coxiella burnetii, the etiological agent of the zoonotic disease Q fever. In this study, we analyzed the molecular activity of the anti-apoptotic T4SS effector protein AnkG (CBU0781) to understand how C. burnetii manipulates host cell viability. We demonstrate by co- and RNA-immunoprecipitation that AnkG binds to the host cell DExD box RNA helicase 21 (DDX21) as well as to the host cell 7SK small nuclear ribonucleoprotein (7SK snRNP) complex, an important regulator of the positive transcription elongation factor b (P-TEFb). The co-immunoprecipitation of AnkG with DDX21 is probably mediated by salt bridges and is independent of AnkG-7SK snRNP binding, and vice versa. It is known that DDX21 facilitates the release of P-TEFb from the 7SK snRNP complex. Consistent with the documented function of released P-TEFb in RNA Pol II pause release, RNA sequencing experiments confirmed AnkG-mediated transcriptional reprogramming and showed that expression of genes involved in apoptosis, trafficking, and transcription are influenced by AnkG. Importantly, DDX21 and P-TEFb are both essential for AnkG-mediated inhibition of host cell apoptosis, emphasizing the significance of the interaction of AnkG with both, the DDX21 protein and the 7SK RNA. In line with a critical function of AnkG in pathogenesis, the AnkG deletion C. burnetii strain was severely affected in its ability to inhibit host cell apoptosis and to generate a replicative C. burnetii-containing vacuole. In conclusion, the interference with the activity of regulatory host cell RNAs mediated by a bacterial effector protein represent a novel mechanism through which C. burnetii modulates host cell transcription, thereby enhancing permissiveness to bacterial infection.
CRIS-Team Scopus Importer:2022-02-25

Truncation of N-terminal regions of Digitalis lanata progesterone 5β-reductase alters catalytic efficiency and substrate preference - Rudolph, Kristin; Bauer, Peter; Schmid, Benedikt; Müller-Uri, Frieder; Kreis, Wolfgang (Biochimie, 2014)